Desymmetrization construction of chiral lactones by synergistic Cu(II) complex and organic base. Issue 29 (16th July 2020) - Ali, Murad; Li, Changkun
Graphical abstract: Highlights: Construction of quaternary carbon center by the desymmetrization strategy. Chiral enol lactones with up to 95% ee could be synthesized from prochiral dialkynoic acid. Synergistic catalysis by chiral Cu(II) complex and chiral (DHQ)2 -PHAL base. Abstract: A highly enantioselective construction of quaternary carbon center has been realized by the desymmetrization strategy. Chiral enol lactones with up to 95% ee could be synthesized from prochiral dialkynoic acid under the catalysis of synergistic chiral Cu(II) complex and chiral (DHQ)2 -PHAL base.